MENINGKATKAN INTEGRITAS LAPORAN KEUANGAN : PERAN MEKANISME GOOD CORPORATE GOVERNANCE, UKURAN PERUSAHAAN, DAN KUALITAS AUDIT - Pratiwi, Yossi Ayu; Anisma, Yuneita; Putra, Adhitya Agri (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2021)
This research examined the effect of Board of Commissioner Independence, Audit Committee, Institutional Ownership, Management Ownership, Company Size, and Audit Quality on Financial Statement Integrity. The population in this study are all BUMN Companies listed in Indonesia Stock Exchange (BEI) in the 2017-2019 period. This research is quantitative research. The type of data used in this study is secondary data from financial statstatements annual reports mentioned above. The sampling method is purposive sampling. The total sample in this study is 15 firms. These data were analyzed using multiple regression analysis with SPSS Version 25. The results of this study showed that Board of Commissioner Independence, Audit Committee, Institutional Ownership, Management Ownership, and Audit Quality affect Financial Statement Integrity, while Company Size does not affect Financial Statement Integrity.